Effects of bergamot (Citrus bergamia) peel oil-supplemented diets on growth performance, haematology and serum biochemical parameters of Nile tilapia (Oreochromis niloticus) - Kesbiç, Osman Sabri; Acar, Ümit; Yilmaz, Sevdan; Aydin, Özlem Durna (Springer Science and Business Media LLC, 2019)
The present study investigated the effects of dietary Citrus bergamia peel oil (CBO) on growth performance, haematological and serum biochemical responses of Nile tilapia, Oreochromis niloticus. Volatile content of C. bergamia peel oil used in study was detected with GC/MS. The 99.47% of the analysed volatile components were identified in decreasing quantities as limonene, linalool and linalyl acetate. The experimental fish were divided into four groups stocked into triplicate tanks (20 fish/tank), and fed daily with an additive-free basal diet containing 0% (CBO0), 0.5% (CBO0.5), 1.0% (CBO1), 2.0% (CBO2) of bergamot peel oil for an 8-week period. Results showed that dietary bergamot peel oil especially at 0.5 g 100 g-1 significantly increased growth performance of fish (p < 0.05). The levels of haemoglobin and haematocrit significantly increased in fish fed with CBO0.5 and CBO1 compared with the CBO0-fed group (p < 0.05), despite no significant difference was observed in CBO2 group (p > 0.05). Highest haematocrit value was found in the CBO0.5 group compared with the control group. The serum glucose of the fish fed with CBO0.5 and CBO1 feeds decreased significantly compared with the control group (p < 0.05). The highest total protein, lowest cholesterol and triglyceride in serum were observed in fish fed with bergamot oil-supplemented groups. According to the results, it was revealed that 0.5% bergamot oil supplementation to Nile tilapia diets optimizes the growth performance, feed utilization and health status related with blood parameters of the fish.
Keywords: Citrus; Dietary Fats, Unsaturated; Dietary Supplements; Animals; Plant Oils; Cichlids; 2. Zero hunger; 6. Clean water